Social representations of Ondas Program teac hers about research (2015)
This article makes known the results of the research on the social representations (SR) regarding the opinion and the stereotype teachers from the central province of Boyacá, belonging to Ondas program, have about the term research. The method used was a case study, and the in-depth interview validated by experts was the instrument. The interviewee’s experiences, which reveal the social representations built about research, are considered in the results. This paper describes, analyzes, and interprets the results of the teacher’s SR and their possible implications when researching on education processes.